2018
DOI: 10.1016/j.ijfoodmicro.2018.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community of industrial raw sausage packaged in modified atmosphere throughout the shelf life

Abstract: Ten lots of industrial raw sausages in modified atmosphere (CO 30%, O 70%), produced in the same plant over 7 months, were analyzed at the day after production (S samples) and at the end of shelf life (E samples), after 12 days storage at 7 °C to simulate thermal abuse. Quality of the products was generally compromised by storage at 7 °C, with only 3 E samples without alterations. During the shelf life, the pH decreased for the accumulation of acetic and lactic acids. A few biogenic amines accumulated, remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…The shelf-life of fresh sausages refrigerator-stored under anaerobiosis depends on the hygienic quality of raw materials, pH, a w , storage temperature, atmosphere, etc. [4]. Some authors, based on the appearance of off-odors and discoloration, have found a shelf-life for these sausages slightly longer than 10 days [3] and others of more than 20 days [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shelf-life of fresh sausages refrigerator-stored under anaerobiosis depends on the hygienic quality of raw materials, pH, a w , storage temperature, atmosphere, etc. [4]. Some authors, based on the appearance of off-odors and discoloration, have found a shelf-life for these sausages slightly longer than 10 days [3] and others of more than 20 days [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…During refrigerated storage of fresh sausages under vacuum or anaerobic MAP, and most probably due to the growth of LAB and Enterobacteriaceae, a significant production of biogenic amines (BA) such as tyramine, putrescine, and cadaverine occurs [4,8]. In a previous study [2], levels of tyramine higher than 100 mg/kg were found in a Mexican fresh sausage stored in anaerobic MAP for more than two weeks, which represents a health risk and corroborates the need to control the production of BA in fresh sausages.…”
Section: Introductionmentioning
confidence: 99%
“…predominant strains (>50% reads) from different batches of Belgian MP samples at the end of their use-by-date (Cauchie et al, 2019). Considered as the main representative spoilage species in meat and meat products (Koort et al, 2005;Liu et al, 2006;Nychas et al, 2008;Pennacchia et al, 2009Pennacchia et al, , 2011Andritsos et al, 2012;De Filippis et al, 2013;Casaburi et al, 2014;Stoops et al, 2015;Zhao et al, 2015;Mann et al, 2016;Stellato et al, 2016;Del Blanco et al, 2017;Geeraerts et al, 2017;Raimondi et al, 2018;Li et al, 2019;Mansur et al, 2019;Peruzy et al, 2019), these bacteria were inoculated on irradiated MP samples, in mono-and in co-culture experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of molecular methods, especially culture-independent approaches, have contributed to the exploration of various food microbiota (Galimberti et al, 2015;Pinu, 2016;Garofalo et al, 2017;Parlapani et al, 2018), as for beverages (Elizaquivel et al, 2015), vegetables Gu et al, 2018;Liu et al, 2019), and for dairy (Nalbantoglu et al, 2014;Riquelme et al, 2015;Ceugniez et al, 2017;Porcellato et al, 2018), seafood Parlapani et al, 2018;Silbande et al, 2018), and meat products (Cocolin et al, 2004;Pennacchia et al, 2011;Nieminen et al, 2012;Benson et al, 2014;Greppi et al, 2015;Polka et al, 2015;Stoops et al, 2015;Zhao et al, 2015;Delhalle et al, 2016;Mann et al, 2016;Carrizosa et al, 2017;Cauchie et al, 2017;Kaur et al, 2017;Korsak et al, 2017;Peruzy et al, 2019;Vester Lauritsen et al, 2019), in order to assess the microbial levels and diversity of food and food products Pothakos et al, 2014;Lee et al, 2017;Rouger et al, 2018). The interest of this method to characterize the dominant spoilage bacteria in pork meat and meat products was also described (Andritsos et al, 2012;Mann et al, 2016;Raimondi et al, 2018;Peruzy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%